The System of Management of the Intangible Assets in the Agricultural Enterprises - CHUB, Yulia V.; TKA, Yarmila S. (Journal of Advanced Research in Law and Economics; Vol 8 No 6 (2017): JARLE Volume VIII Issue 6(28) Fall 2017, 2017)
For Ukraine, the need for intellectual property management is relevant, as the country announced an innovative way of economic development, which is the foundation of intellectual property. Modern developments of agricultural enterprises are based on the principles of sustainable management, competitive production and effective use of intellectual capital. Market relations need to strengthen the role of intangible assets as well as intellectual property management, thus becoming an important part of strategic management company and closely associated with the main directions of its activities. Formation of these areas and the timing of their reach – are tasks to be solved by management using strategic management. Intangible assets management business is gradually becoming a factor of sustainable development that enhances the market value of enterprises and formation of competitive advantage